Prospective evaluation of clinical and radiologic factors predicting return to activity within 6 months after arthroscopic rotator cuff repair - Collin, Philippe; Abdullah, Arifaizad; Kherad, Omar; Gain, Solenn; Denard, Patrick J.; Ladermann, Alexandre (Elsevier, 2015)
Background This study aimed to report the outcome of patients who underwent arthroscopic rotator cuff repair (ARCR) and to determine the factors associated with return to work and activity. Materials Three hundred sixty-five patients who underwent ARCR were prospectively evaluated. The cohort was divided into 2 groups based on clinical results at 6 months. Group A consisted of patients who were considered to have a satisfactory outcome based on return to their previous professional or spare-time activities. Group B consisted of patients with an unsatisfactory outcome based on a lack of return to normal work or activities. Results Of the patients, 305 had a satisfactory outcome (group A) and 60 were categorized as having an unsatisfactory outcome (group B). On multivariate analysis, preoperative factors associated with group B included female gender and heavy manual labor. Postoperative bursitis on ultrasound at 6 months was associated with being in group B. Lack of tendon healing was not associated with group B. However, if a patient without healing had persistent pain at 6 months, the pain persisted at 9 months. Conclusion ARCR is an effective procedure that leads to significant improvement in pain, function, and tendon healing in most cases. However, in 1 of 5 cases, patients were unable to resume normal activity at 6 months postoperatively. Persistent limitation at 6 months was associated with female gender, heavy manual workers, and the presence of postoperative persistent bursitis.